(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Appreciation for minors’ involvement in clinical trials and for children’s autonomy is growing, but has to be combined with the parental and social duty to protect them. In recent years the ethical debate had shifted to specifically encouraging children’s inclusion in trials, taking into account the benefit they can obtain, both direct and indirect. Nevertheless, there is a risk concerning the protection of children’s rights and the proper acquisition of informed consent could become a legal and ethical issue. The article examines the ethical framework concerning informed consent in paediatric clinical trials at European level, with special reference to guidelines, recommendations and opinions issued by national, European and international bioethics/research ethics committees, scientific societies, European institutions and international organizations. The review aims at pointing out key issues regulated by common ethical standards and grey areas in which soft law regulation is still evolving. The focus is devoted to the topics of assent, parental permission and shared decision-making, analysed in the light of the general principle of child’s best interest.